Pemahaman Alat Keselamatan Di Kapal Penangkap Ikan Di Kecamatan Bonto Bahari Kabupaten Bulukumba - Deselfia DNM Sahari; Mariani Loise; St. Syahriati; Andi Herlina; Darwis Darwis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Fishermen along the river in the Bonto Bahari sub-district utilize small boats, often called kettles, to find and catch fish. However, these fishermen pay little attention to safety while sailing without using safety equipment. Boat accidents on the river still often occur along the waters they catch fish because of the lack of safety equipment available on board. The purpose of this service is to provide material on how to prepare safety equipment on the ship and how to use good and correct safety equipment as it should be based on the provisions or experience of the speaker. The method used in this activity is the lecture and discussion method at group meetings, as the target of counseling is fishermen members using broadcast media in the form of power points and YouTube links. The results of community service activities regarding health education (counseling) on Understanding Safety Equipment on Fishing Vessels in Bonto Bahari District, Bulukumba Regency have been carried out well and received an enthusiastic response from the people of Bonto Bahari District.